Longitudinal Pure‐Tone Threshold Changes in the Same Subjects: Analysis of Factors Affecting Hearing. (12th September 2018) - Kim, Hantai; Lee, Jung‐Jun; Moon, Yeorae; Park, Hun Yi
Abstract : Objectives: To investigate the change of hearing threshold over time and analyze factors that could affect hearing, this longitudinal study of pure‐tone threshold changes in the same subjects at a 9‐year interval was performed. Study Design: Retrospective longitudinal study in a single center (n = 1, 978). Methods: A total of 1, 978 subjects were included; they received pure‐tone audiometry at a 9‐year interval. The degree of the threshold changes was examined and compared between age groups. The subjects' data, such as the level of cholesterol, were analyzed to find risk factors on hearing. Results: The average of the threshold changes was 3.35 dB in the 20s to 30s; 4.38 dB in the 30s to 40s; 5.75 dB in the 40s to 50s; 7.21 dB in the 50s to 60s; and 10.00 dB in the 60s to 70s (all P  < 0.05). If the low‐density lipoprotein cholesterol (LDL‐C) was maintained below 100 mg/dl, the difference in the weighted four‐frequency average was 5.45 dB, whereas it was 6.15 dB in the subjects whose LDL‐C was over 100 mg/dl ( P  = 0.032, age‐adjusted). In current smokers, the thresholds increased more than in never‐ or ex‐smokers ( P  = 0.026 in the weighted four‐frequency average and P  = 0.011 at 8, 000 Hz, age‐adjusted). Conclusion: The degree of the threshold changes exhibited an exponential increase with age. Cessation of smoking is advisable to prevent increased aggravation of hearing. Strict management of the low‐density lipoprotein cholesterol may have a positive effect on hearing. Level of Evidence: 3 Laryngoscope, 129:470–476, 2019